CSF Cholinergic Index, a New Biomeasure of Treatment Effect in Patients With Alzheimer’s Disease - Karami, Azadeh; Eriksdotter, Maria; Kadir, Ahmadul; Almkvist, Ove; Nordberg, Agneta; Darreh-Shori, Taher (Frontiers in Molecular Neuroscience, 2019)
Alzheimer’s disease (AD) is a progressive disease with early degeneration of the central cholinergic neurons. Currently, three of four AD drugs act by inhibiting the acetylcholine (ACh) degrading enzyme, acetylcholinesterase (AChE). Efficacy of these drugs depends on available amount of ACh, which is biosynthesized by choline acetyltransferase (ChAT). We investigated whether treatment with a cholinesterase-inhibitor, galantamine, alters the relative levels of AChE to ChAT in CSF and whether levels of these CSF biomarkers correlate with in vivo AChE activity and nicotinic binding sites in the brain assessed by PET. Protein concentrations and activities of ChAT and AChE were measured in cerebrospinal fluid of 18 patients with mild AD prior to and after 3 months of treatment with galantamine (n=12) or placebo (n=6), followed by 9 additional months of galantamine treatment in all patients. A Cholinergic index was defined as the ratio of ChAT to AChE in CSF and was evaluated in relation to the in vivo AChE activity, the nicotinic binding sites and different measures of cognition. Besides an expected inhibition of AChE activity, galantamine treatment was accompanied by a mild increase in CSF ChAT activity. Thereby, the Cholinergic index was significantly increased in the Galantamine group (60% ±14) after 3 months compared to baseline (p< 0,0023) or the Placebo-group (p<0.0004). This index remained high in the Galantamine-group compared to baseline (54% ±11) at 12 month follow-up, while it showed an increase in the Placebo-group when they switched to active galantamine treatment (44% ±14 versus baseline, 61%±14 versus 3 months, all p-values<0.05). Furthermore, the in vivo brain AChE activity (assessed by PET) correlated with the CSF Cholinergic index at 12 months (r= 0.98, p<0.001). The CSF Cholinergic index also correlated with ADAS-Cog and some other neuropsychological tests at 12 months. This is the first study assessing a CSF Cholinergic index in relation to treatment with a cholinesterase inhibitor. The treatment-specific increase in CSF ChAT activity suggests that cholinesterase-inhibitors may also increase the acetylcholine-biosynthesis capacity in the patients. Additional studies are warranted to evaluate utility of the CSF Cholinergic index as a biomeasure of therapeutic effect in AD.